Numerical study on heat storage efficiency of broken rock mass under different CO2 injection conditions - Geng, Haozhe; Wu, Yu; Hao, Guan; Hao, Yang; Li, Decheng; Zhou, Haiyang (Frontiers in Earth Science, 2023)
The application of energy storage technology can solve the problems of randomness and volatility in the development and use of renewable energy, such as wind and solar energy, and effectively improve energy utilization. Rock heat storage is one of the primary forms of sensible heat storage. The heat storage efficiency and heat storage capacity of rock packed bed are important indicators to measure the energy storage effect of a rock energy storage system. This paper takes CO2 as the heat-carrying medium and broken granite grains as the packed bed matrix of the energy storage system. It establishes a porous medium thermal-hydraulic-mechanical coupling model of the broken rock bed. The heat injection and production process of the large-sized rock bed heat storage system is simulated using the COMSOL finite element software, and the heat storage efficiency and heat storage capacity of the broken rock bed is analyzed under different fluid injection pressures and injection temperatures. The results show that: (1) With the increase of CO2 injection pressure, the heat storage and heat production speed of the heat storage system will increase, and the heat storage rate changes from two stages of "low rise - slow decline" to four stages of "rapid increase - stability - rapid decrease - stability"; (2) With the increase of CO2 injection temperature, the maximum heat storage capacity of the rock bed heat storage system will increase. Due to the increase in the temperature gradient between CO2 and the rock bed, the heat storage and the heat production time of the heat storage system will increase, and its speed will decrease.